Preparation method of reinforced and toughened wood based on carbon quantum dots

The method of modifying wood with surface ion-modified carbon quantum dots solves the problems in the existing technology that wood modification leads to a decrease in toughness and strength-to-weight ratio. It achieves a simultaneous improvement in the dimensional stability, strength and toughness of wood, and maintains A high strength-to-weight ratio.

CN119347906AActive Publication Date: 2025-01-24BEIJING FORESTRY UNIVERSITY
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411821203.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-11
Publication Date
2025-01-24
Estimated Expiration
2044-12-11

AI Technical Summary

Technical Problem

When existing wood modification methods improve strength and dimensional stability, they usually lead to a decrease in toughness and the strength-to-weight ratio of the modified material decreases, losing the unique advantages of the wood itself.

Method used

The carbon quantum dot modified by the surface ion is used as a modified agent, and the wood is treated through the vacuum pressure impretion method to regulate the micro -structure of the cell wall and increase the enlargement of the crystallinity and the cell cavity. promote.

Benefits of technology

Under the premise that the overall size and quality of the wood are not large, the size of the wood is stable, intensity, and toughness, and maintains a highly strong ratio, and enhances the overall performance of the wood.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119347906A_ABST
    Figure CN119347906A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of wood modification, and particularly relates to a preparation method of reinforced and toughened wood based on carbon quantum dots. The preparation method comprises the following steps: treating a test material by using a carbon quantum dot modification liquid through a vacuum pressure impregnation method; sealing the end part of the wood by using an end sealing material, and placing the wood at room temperature for a period of time; and finally, the wood is placed in a drying box or a drying kiln to be heated and dried, and therefore the carbon quantum dot modified wood is obtained. Wherein the carbon quantum dots are surface ion modified carbon quantum dots; the concentration of the carbon quantum dot modified liquid is 0.1-5% (in percentage by mass). The preparation method of the carbon quantum dots is simple, free of solid byproducts and short in time consumption. The wood is directly modified through the carbon quantum dots, the preparation process is simple, the modification liquid concentration is low, cost is low, and large-scale application and popularization can be achieved. According to the prepared modified wood, the absolute value of cell wall crystallinity can be increased, cell cavities can be enlarged, on the premise that the overall size and quality of the wood are not greatly changed, the dimensional stability, strength and toughness of the wood are synchronously improved, and the strength-weight ratio of the wood is increased.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a preparation method of reinforced and toughened wood based on carbon quantum dots, belonging to the technical field of wood modification. Background Art

[0002] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention, and should not necessarily be regarded as an admission or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.

[0003] Wood is a renewable, recyclable and eco-friendly material. It is highly regarded for its beautiful texture, high strength-to-weight ratio, and easy processing. It is the first choice for construction, furniture and other applications. However, hemicellulose, the main component of wood, has strong hygroscopicity, which makes it unstable in size, easy to deform and crack, and causes microbial deterioration such as mildew and decay. Therefore, in order to avoid these problems, wood needs to be modified.

[0004] At present, the modification methods that can simultaneously improve the strength and dimensional stability of wood include resin impregnation (phenolic resin, etc.), monomer impregnation (furfuryl alcohol, 1.3-dimethanol-4.5-dihydroxyethylene urea, etc.) and cross-linking modification (glutaraldehyde, etc.). These methods have shown good results in dimensional stability and mechanical properties (such as surface hardness and compressive strength), but the toughness of most modified materials has decreased to varying degrees. For example, in phenolic resin modification, when the density of the modified material increases by 15%, the toughness decreases by 43%. When the weight gain rate of furfuryl alcohol modified material reaches 70%, the impact toughness of the wood will decrease by 57%. This adverse effect was also observed in furfuryl alcohol modified materials with lower weight gain rates. After modification with glutaraldehyde at a concentration of 0.4M, the toughness of the wood decreased by more than 60%. In addition, the performance improvement effect of these modified materials is usually inseparable from the weight gain rate, resulting in a significant decrease in the strength-to-weight ratio of the modified material compared with the unmodified wood, and losing the unique advantage of the high strength-to-weight ratio of the wood itself.

[0005] Carbon quantum dots (CQDs) are a type of zero-dimensional carbon nanomaterial, mainly composed of C, H and O elements. It has good hydrophilicity, low toxicity, and a wide range of synthetic raw materials and simple synthesis methods. Studies have shown that CQDs can significantly change the physical and chemical structure of wood cellulose. In addition, surface ion modification helps to enhance the hydrogen bonding between carbon quantum dots and wood components. The inherent properties of CQDs and the modification of cellulose by CQDs make this study a reasonable choice of surface ion-modified CQDs as a modifier. Therefore, this study used surface ion-modified carbon quantum dots to directly modify wood. By regulating the microstructure of the cell wall, the absolute value of the crystallinity of the wood cell wall and the expansion of the cell cavity were increased. Under the premise that the overall size and quality of the wood did not change much, the dimensional stability, strength and toughness of the wood were simultaneously improved, and the strength-to-weight ratio of the wood was improved. Summary of the invention

[0006] The purpose of the present invention is to prepare light, high-strength and high-toughness wood, and to achieve simultaneous improvement of wood dimensional stability, strength and toughness under the premise that the overall size and quality of the wood do not change much. A method for strengthening and toughening wood based on carbon quantum dots is provided, comprising the following steps:

[0007] Step 1, preparation of carbon quantum dot modified liquid. Carbon quantum dots can be prepared by the method of patent application number 202411000022.8, entitled "An ion-based carbon quantum dot and its application in resin curing". Use polybasic organic acid and fluoroborate as raw materials, fully dissolve them by ultrasound, and then heat them in a microwave oven for 3 to 10 minutes to obtain surface ion-modified carbon quantum dots. Then, mix the carbon quantum dots and ultrapure water in a certain proportion to obtain a carbon quantum dot modified liquid;

[0008] Step 2, wood processing and characterization, select wood without bark, if it is a heartwood species, try to choose the sapwood part, and saw the wood into test pieces of a certain size;

[0009] Step 3, vacuum pressure impregnation of wood, treat the wood with the carbon quantum dot modified liquid by vacuum pressure impregnation method. After impregnation, wipe the excess modifier on the surface with a paper towel. In order to promote the entry of the modifier into the cell wall and avoid the end water moving too fast, the end of the wood is sealed and left at room temperature for a period of time to diffuse and air dry. Then, the wood is placed in a drying oven for drying to obtain a carbon quantum dot modified material. The physical and mechanical properties of the modified material, including impact toughness, flexural strength and elastic modulus, compressive strength and dimensional stability, are improved.

[0010] Preferably, in step 1, the concentration of the carbon quantum dot modification solution is 0.1% to 5% by mass.

[0011] Preferably, in step 2, broad-leaved wood, such as poplar, oak, eucalyptus, etc., is included, and coniferous wood, such as fir, radiata pine, Scotch pine, etc. is also included.

[0012] Preferably, in the step 3, the specific method of vacuum pressure impregnation is to first perform vacuum treatment for 30 to 60 minutes under a vacuum degree of 0 to -0.1 MPa, then introduce the carbon quantum dot modification liquid, and then perform pressure treatment for 60 to 120 minutes under a pressure of 0 to 2 MPa. Further preferably, the vacuum degree is -0.05 to -0.1 MPa, and the pressure is 0.5 to 2 MPa.

[0013] Preferably, in step 3, after the wood is treated by vacuum pressure impregnation and before drying, the end-capping material is one or more of tin foil, tin foil tape, epoxy resin, and polyethylene glycol, and the room temperature placement time is 24 to 72 hours.

[0014] Preferably, in step 3, the drying procedure is to first treat at 40-80°C for 1-6 hours, then treat at 80-105°C for 9-24 hours, remove the end-capping material, and finally dry at 80°C to absolute dryness;

[0015] A carbon quantum dot modified material prepared by the above method.

[0016] The beneficial effects of the present invention are:

[0017] The carbon quantum dots of the present invention are simple to prepare, have no solid byproducts, and are time-saving. The carbon quantum dots of the present invention are ion-modified, and the surface contains abundant hydroxyl, carboxyl, fluoroborate anions and cations, which can enhance the hydrogen bonding between the carbon quantum dots and wood components.

[0018] The present invention adopts carbon quantum dots to directly modify wood, has a simple preparation process, low concentration of modified liquid, low cost, and can be widely promoted and applied.

[0019] The modified material of the present invention maintains its unique advantage of high strength-to-weight ratio under the premise that the overall size and quality of the wood do not change much, achieves simultaneous improvement of the dimensional stability, strength and toughness of the wood, and can increase the absolute value of the crystallinity of the wood cell wall and the expansion of the wood cell cavity. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 It is a schematic diagram of the bending strength and elastic modulus of the comparative example and embodiments 1, 2 and 3.

[0021] Figure 2 It is a schematic diagram of the compressive strength along the grain of the comparative example and embodiments 1, 2 and 3.

[0022] Figure 3 It is a schematic diagram of the impact toughness of the comparative example and embodiments 1, 2 and 3.

[0023] Figure 4 It is a schematic diagram of the strength-to-weight ratio of the comparative example and embodiments 1, 2, and 3.

[0024] Figure 5 It is a schematic diagram of the dimensional stability of Examples 1, 2, and 3. DETAILED DESCRIPTION

[0025] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments. The embodiments provide detailed implementation methods and specific operating processes, but the protection scope of the present invention is not limited to the following embodiments.

[0026] Example 1

[0027] Preparation of carbon quantum dot modified solution: 3 parts of citric acid and 1 part of sodium fluoroborate were used as raw materials, and after being fully dissolved by ultrasound, they were placed in a microwave oven and heated for 5 minutes to obtain surface ion-modified carbon quantum dots. According to the mass percentage, a glass rod was used to stir and a carbon quantum dot modified solution with a concentration of 0.5% was prepared to obtain a uniform light yellow clear solution;

[0028] Wood processing and characterization: Populus cathayana was selected and the wood was sawn into test materials with sizes of 20 mm (axial) × 20 mm (tangential) × 20 mm (radial), 80 mm (axial) × 10 mm (tangential) × 4 mm (radial), and 30 mm (axial) × 20 mm (tangential) × 20 mm (radial);

[0029] Vacuum pressure impregnation of wood: vacuum treatment for 45 minutes under vacuum degree -0.1MPa, then introduce carbon quantum dot modification liquid, and then pressurize for 90 minutes under pressure of 0.5MPa. After impregnation, wipe the excess modifier on the surface with a paper towel. In order to promote the entry of the modifier into the cell wall and avoid the rapid movement of moisture at the end, seal both ends of the wood with tin foil and place it at room temperature for 24 hours for diffusion and air drying. Then, place the wood in a drying oven for drying: first treat it at 80℃ for 1 hour, and then treat it at 105℃ for 10 hours. Remove the tin foil and finally dry it at 80℃ to absolute dryness to obtain carbon quantum dot modified material.

[0030] Example 2

[0031] Preparation of carbon quantum dot modified solution: 3 parts of citric acid and 1 part of sodium fluoroborate were used as raw materials, and after being fully dissolved by ultrasound, they were placed in a microwave oven and heated for 5 minutes to obtain surface ion-modified carbon quantum dots. According to the mass percentage, a glass rod was used to stir and a carbon quantum dot modified solution with a concentration of 1% was prepared to obtain a uniform light yellow clear solution; then the wood was vacuum-pressurized and impregnated as in Example 1.

[0032] Example 3

[0033] Preparation of carbon quantum dot modified solution: 3 parts of citric acid and 1 part of sodium fluoroborate were used as raw materials, and after being fully dissolved by ultrasound, they were placed in a microwave oven and heated for 5 minutes to obtain surface ion-modified carbon quantum dots. According to the mass percentage, a glass rod was used to stir and a carbon quantum dot modified solution with a concentration of 2% was prepared to obtain a uniform light yellow clear solution; then the wood was vacuum-pressurized and impregnated as in Example 1.

[0034] Comparative Example

[0035] The untreated wood was dried at 103°C until it was absolutely dry, and physical and mechanical test specimens of the above dimensions were prepared.

[0036] After modification, the weight gain rate, volume increase rate and density change rate of Examples 1, 2 and 3 are shown in Table 1. After modification with carbon quantum dots, the weight gain rate and volume increase rate of the wood are small, which shows that the overall size and quality of the wood do not change significantly. The density of Example 1 is basically unchanged, while the density of Examples 2 and 3 increases slightly, which shows that the modified material still maintains the advantage of light weight of wood. Table 1 Weight gain rate, volume increase rate and density change rate of Examples 1, 2 and 3

[0037] Figure 1 It is a schematic diagram of the bending strength and elastic modulus of the comparative example and embodiments 1, 2, and 3. It can be seen that the bending strength does not change much, while the elastic modulus is significantly improved, up to 70%, indicating that the carbon quantum dot modification effectively improves the stiffness of the wood. This is mainly because the carbon quantum dots cross-link the cellulose, making the cell wall structure more compact and able to withstand greater forces without being easily deformed.

[0038] Figure 2 It is a schematic diagram of the compressive strength along the grain of the comparative example and Examples 1, 2, and 3. It can be seen that the compressive strength along the grain is significantly improved, indicating that the carbon quantum dot modification can effectively improve the strength of the wood. This is mainly because the hydrogen bonds between the carbon quantum dots and cellulose cross-link the cellulose and change the cell wall structure of the wood.

[0039] Figure 3 It is a schematic diagram of the impact toughness of the comparative example and Examples 1, 2, and 3, from which it can be seen that the impact toughness is significantly improved, indicating that the present invention can effectively improve the strength and toughness of wood at the same time. This is mainly because the carbon quantum dots cross-link the cellulose, reduce the distance between microfibrils, and densify the cell wall. This is different from the previous cell wall expansion, the distance between microfibrils increases, which is not conducive to stress transmission and transfer.

[0040] Figure 4 It is a schematic diagram of the strength-to-weight ratio of the comparative example and embodiments 1, 2 and 3. It can be seen from the figure that the strength-to-weight ratio is significantly improved, indicating that the present invention not only improves the strength and toughness of the wood, but also improves the strength-to-weight ratio of the wood.

[0041] Figure 5 Schematic diagram of the dimensional stability of Examples 1, 2, and 3, from which it can be seen that the carbon quantum dot modified materials can improve the dimensional stability of wood, and the dimensional stability of Example 3 is better, which is due to the larger capacity increase rate of Example 3.

Claims

1. A method for preparing reinforced and toughened wood based on carbon quantum dots, characterized in that: The carbon quantum dot modified liquid is treated with wood by vacuum pressure impregnation method, and then the ends of the wood are sealed with a sealing material and left at room temperature for a period of time. Finally, the wood is placed in a drying oven or a drying kiln for heating and drying to obtain a carbon quantum dot modified material.

2. The method for preparing carbon quantum dot reinforced and toughened wood according to claim 1, characterized in that: The carbon quantum dots are carbon quantum dots modified with surface ions; the carbon quantum dots and water are mixed in a certain proportion to obtain the carbon quantum dot modified solution.

3. The method for preparing carbon quantum dot reinforced and toughened wood according to claim 2, characterized in that: Calculated by mass percentage, the concentration of the carbon quantum dot modification solution is 0.1-5%.

4. The method for preparing carbon quantum dot reinforced and toughened wood according to claim 1, characterized in that: The procedure of the vacuum pressure impregnation method is to first perform vacuum treatment for 30 to 60 minutes at a vacuum degree of 0 to -0.1 MPa, then introduce the carbon quantum dot modification solution, and then perform pressure treatment for 60 to 120 minutes at a pressure of 0 to 2 MPa.

5. The method for preparing carbon quantum dot reinforced and toughened wood according to claim 1, characterized in that: The end-capping material is one or more of tin foil, tin foil tape, epoxy resin, and polyethylene glycol, and the room temperature placement time is 24 to 72 hours.

6. The method for preparing carbon quantum dot reinforced and toughened wood according to claim 1, characterized in that: The drying procedure is to first treat at 40-80°C for 1-6 hours, then treat at 80-105°C for 9-24 hours to remove the end-capping material, and finally dry at 40-80°C to constant weight.

7. A wood prepared by the method for preparing reinforced and toughened wood based on carbon quantum dots according to any one of claims 1 to 6.

Citation Information

Patent Citations

  • High-hygroscopicity wood and manufacturing method

    CN114131715A

  • Carbon quantum dot with ionic liquid structure as well as preparation method and application of carbon quantum dot

    CN114149332A

  • Ion-based carbon quantum dot and application thereof in resin curing

    CN118956387A